Bioactive compounds from marine sponges: fundamentals and applications - Varijakzhan, Disha; Jiun, Yan Loh; Wai, Sum Yap; Yusoff, Khatijah; Seboussi, Rabiha; Swee, Hua Erin Lim; Kok, Song Lai; Chong, Chou Min (Multidisciplinary Digital Publishing Institute, 2021)
Marine sponges are sessile invertebrates that can be found in temperate, polar and tropical regions. They are known to be major contributors of bioactive compounds, which are discovered in and extracted from the marine environment. The compounds extracted from these sponges are known to exhibit various bioactivities, such as antimicrobial, antitumor and general cytotoxicity. For example, various compounds isolated from Theonella swinhoei have showcased various bioactivities, such as those that are antibacterial, antiviral and antifungal. In this review, we discuss bioactive compounds that have been identified from marine sponges that showcase the ability to act as antibacterial, antiviral, anti-malarial and antifungal agents against human pathogens and fish pathogens in the aquaculture industry. Moreover, the application of such compounds as antimicrobial agents in other veterinary commodities, such as poultry, cattle farming and domesticated cats, is discussed, along with a brief discussion regarding the mode of action of these compounds on the targeted sites in various pathogens. The bioactivity of the compounds discussed in this review is focused mainly on compounds that have been identified between 2000 and 2020 and includes the novel compounds discovered from 2018 to 2021.